Serodiagnosis of urogenital schistosomiasis and profiling of immunoreactive protein(s) in Schistosoma haematobium soluble egg and adult worm antigens - Kabirat A Sulaiman; Tajudeen O Oriade; Timothy Auta; Funmilayo I D Afolayan; Alexander B Odaibo; Rafaella FQ Grenfell; Ramzy G Fatem; Oyetunde T Oyeyemi (Journal of Vector Borne Diseases, 2025)
Background & objectives: To achieve schistosomiasis eradication plan by 2030, the development of efficient diagnosis is crucial. This study focuses on assessing the immunodiagnostic potential of S. haematobium (Sh) soluble egg antigen (SEA) and worm antigen (SWA) for urogenital schistosomiasis. Methods: Urine microscopy identified 50 S. haematobium-positive and 50 negative samples from a total of 500 examined. An additional 50 samples from a non-endemic area were included, bringing the total number of samples used for the assay to 150. Indirect ELISA immunoassays using SEA and SWA as the probing antigens evaluated 50 sera samples each from Sh positive, negative endemic (NE), and non-endemic (NNE) individuals. SDS-PAGE analysis of crude protein extracts was conducted, followed by Western blot analysis using primary antibodies from pooled Sh-infected sera samples. Results: Diagnostic performance was evaluated using the area under the receiver operating characteristic (ROC) curve (AUC), sensitivity, and specificity. The AUC values for Sh SEA and SWA were 0.75 and 0.76 in NE samples, and 0.91 and 0.89 in NNE samples, respectively. Sensitivities 90 (95% CI: 78.64–95.65)/ 64.71 (95% CI: 52.17–75.92), and specificities 50 (95% CI: 36.64–63.36)/ 81.25 (95% CI: 63.56–92.79) were recorded for SEA and SWA, respectively in NE samples. In addition, sensitivities 90 (78.64–95.65)/ 92 (95% CI: 80.77–97.78), and specificities 72 (95% CI: 58.33–82.53)/ 72.00 (95% CI: 57.51–83.77) were recorded for SEA and SWA, respectively in NNE samples. The mean antibody titer against Sh SEA in infected samples was significantly higher than in non-infected samples (P <0.0001). Eight immunoreactive protein bands; four each of SEA and SWA were identified, indicating potential for diagnostic tool development. Interpretation & conclusion: Sh SEA and SWA demonstrate promise for diagnosing urogenital schistosomiasis in both endemic and non-endemic regions.